Proceso de atención de enfermería en gestante de 37 semanas, con diabetes gestacional. - Anchundia Álava, Sander Javier (2022)
The present work is a clinical case study carried out during hospital internship practices, in which the problem of a 30-year-old female patient in a third-trimester state of pregnancy, who presents gestational diabetes as a comorbidity, was analyzed. The main objective was the execution of the nursing care process in the mentioned case. The bibliographic review, nursing interventions, based on the clinical history of the pregnant woman with gestational diabetes was used. The main results obtained are: It was possible to apply the nursing care process, in addition to the corresponding interventions, to prevent neonatal maternal complications. We conclude that gestational diabetes is a disease related to obesity and the patient's history. These cases must be referred to a tertiary care center that has intensive postnatal care to protect the life of the product.